Fluorescence Detection of Etoposide Encapsulated Mesoporous Silica Nanoparticles by Environmentally Benign Bioanalytical HPLC Method and its Application to Pharmacokinetic Study - Saroj, Seema; Shah, Priya; Rajput, Sadhana J. (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Etoposide belongs to BCS Class IV suffering from solubility and permeability limitations. Thereby, hindering its bioavailability. Thereby, it is imperative to enhance its bioavailability by suitable formulation to achieve a desired therapeutic effect. Objectives: In present work, ETD was encapsulated into mesoporous silica nanoparticles (MSNs) with the aim of achieving bioavailability enhancement. Further, A simple, efficient, and environmentally benign HPLC method with highly sensitive fluorescence detection was developed for determination of Etoposide (ETD) in the mice plasma. Materials and Methods: The developed HPLC-FL method was sensitive enough to detect etoposide in the nano formulation in a plasma matrix with a high degree of accuracy and precision, taking Tapentadol as an internal standard. The chromatographic separation was conducted on a Waters symmetry C18 column with a mobile phase composition of methanol:formate buffer (20mM) pH 3.9 in ratio 51:49 at a flow rate of 1 mL/min with excitation wavelength fixed at 247 nm and emission measured at 323 nm. Plasma sample pre-treatment was done following protein precipitation method. The developed bioanalytical method was validated successfully. Green metric assessment was done and Eco-indicators were employed which suggested the Eco-friendliness of developed method as well as supremacy over those available so far. Results: The bioavailability was enhanced 4.35 times as compared to ETO alone. The pharmacokinetic parameters of orally administered MSNs formulation were t1/2 (Half-life) 12.12 hr, Peak plasma concentration Cmax 3.98, Area Under the Curve (AUC) 52.78 and Mean Residence Time 18.23 hr. Conclusion: It could be concluded that the developed mesoporous formulation played a major part in BA enhancement of ETD and the developed green method was highly efficient to serve the purpose of ETD determination from biological matrix.
Keywords: Etoposide; Mesoporous silica nanoparticles; Green metrics assessment; Pharmacokinetic study; Bioavailability enhancement